PENGEMBANGAN PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO DALAM UPAYA PEMBANGUNAN EKONOMI DAERAH PEDESAAN DI KECAMATAN MEMPAWAH HULU KABUPATEN LANDAK - B61111028, RINI SULISTIAWATI ANSFRIDUS. J. ANDJIOE (Jurnal Ekonomi Daerah (JEDA), 2013)
ABSTRACTUntil this moment, the raising of electrical energy production which is produced byPLN; is not able to afford the electrical needs of the West Borneo civils in general, alongwith Landak regency. This thing is mainly caused by the limitedness of diesel fuel suppliesaround the West Borneo region and affects the provision of electrical energy. Water isrenewable natural resources that is commonly found in West Borneo villages. This kind ofpotential can be utilized as the source of energy to support the process of constructionwithin villages in terms of incresing villages prosperity. Mempawah Hulu subdistrict,Landak regency, has a huge potential of the Micro Hydro Energy Power Plant (PLTMH).This opportunity can be developed as one of the alternatives in providing electrical energyfor villages, especially for those who lived in a no-electric region.The purposes of this research are : to analyse the potential of water in MempawahHulu he potential of water utilization for the development of Micro Hydro Energy PowerPlant in Mempawah Hulu subdistrict, Landak Regency, to analyse the development ofelectrical construction using the micro hydro energy in terms of expanding the productiveeconomical activities in Landak regency, also knowing the complexions of Micro HydroEnergy Power Plant development in Mempawah Hulu subdistrict, Landak regency. Theresults of this research are :1. The construction of PLTMH in Mempawah Hulu is one of the appropriatealternatives because it is supported by the renewable natural resource called water.Besides, the PLTMH project requires a small amount of money.2. The PLTMH is a project which is environmentally friendly and doesnt produce airand sound pollution respectively.3. Its operational and maintenance fees are cheaper compare to diesel machine thatneeds fossils energy to be operated.4. The provision of water in several waterfalls which is located in Mempawah Hulusubdistrict is adequate enough to construct PLTMH is small range according to thecivils needs.5. Every single community that enjoy the benefits of the PLTMH construction is able tokeep the condition of natural resources and environment that provides the water.6. The plan of PLTMH project construction in Mempawah Hulu subdistrict will carrypositive effects particularly in : supporting the growth of households industry,increasing family incomes, giving larger opportunities for students to have a bettereducation and giving an ease for people to access informations from the outside.